Applying Theory of Constraints to Timber Harvesting: A Case Study from the Northeast USA - René H. Germain; Matthew C. Kelly (Croatian Journal of Forest Engineering, 2020)
Logging firms are a critical link in wood supply chains, connecting forest landowners with markets for wood products. Improving operational planning can benefit individual logging firms as well as the larger wood supply chain in which they operate. Applying concepts from Theory of Constraints (TOC) to timber harvesting may help achieve greater predictability and efficiency when planning harvest operations. However, examples that demonstrate how TOC can improve logging operations are lacking. This study focuses on the analysis of production and activity data collected during the harvest of a temperate mixed hardwood forest in the Northeast United States using a chainsaw-forwarder system through a TOC lens. Specifically, the drum-buffer-rope (DBR) method was used to reschedule operator and machine activities such that a consistent flow of wood from stump to landing was maintained despite anticipated production setbacks. The results of this case study provide insights into the usefulness of applying TOC to logging operations. In particular, logging businesses must be able to estimate machine and operator productivity within a given harvest context to identify and exploit system constraints, while taking full advantage of unused capacity of any non-constraint functions.